Cardioprotective effects of transplanted adipose‐derived stem cells under Ang II stress with Danggui administration augments cardiac function through upregulation of insulin‐like growth factor 1 receptor in late‐stage hypertension rats. Issue 7 (21st April 2021) - Barik, Parthasarathi; Shibu, Marthandam Asokan; Hsieh, Dennis Jine‐Yuan; Day, Cecilia Hsuan; Chen, Ray‐Jade; Kuo, Wei‐Wen; Chang, Yung‐Ming; Padma, V. Vijaya; Ho, Tsung‐Jung; Huang, Chih‐Yang
Abstract: In aging hypertensive conditions, deterioration of insulin‐like growth factor 1 receptor (IGF1R) cause a pathological impact on hypertensive hearts with an increased Ang II level. Recovering these adverse conditions through transplanted adipose‐derived stem cells is a challenging approach. Moreover, Danggui, a Traditional Chinese medicine (TCM), is used for the treatment of cardioprotective effects. In this study, to evaluate whether the combined effect of MSCs and TCM can recover the cardiac function in late‐stage hypertension rats. We observed that lower dose of Danggui crude extract treatment showed an increased level of cell viability with maintained stemness properties and growth rate in rat adipose‐derived stem cells (rADSCs). Further, we cocultured the H9c2 cells with rADSCs and the results revealed that Danggui ‐treated MSCs enhanced the IGF1R expression and attenuated the hypertrophy in H9c2 cells against Ang II challenge by immunoblot and rhodamine‐phalloidin staining. In addition, Danggui crude extract was also quantified and characterized by HPLC and LC–MS analysis. Furthermore, the in vivo study was performed by considering 11 months old rats ( n = 7). Importantly, the oral administration of Danggui crude extract with stem cells intravenous injection in SHR‐D‐ADSCs group showed a combination effect to augment the cardiac function through enhancement of ejection fraction, fractional shortening, contractility function in the late‐stage hypertension conditions. We have also observed a decreased apoptosis rate in the heart tissue of SHR‐D‐ADSCs group. Taken together, these results indicate that the combinatorial effects of Danggui crude extract and stem cell therapy enhanced cardiac function in late‐stage SHR rats.